Sukuk securities : new ways of debt contracting - Safari, Meysam; Ariff, Mohamed; Shamsher Mohamad (Singapore : Wiley, 2014)
The essential guide to global sukuk markets worldwideSukuk Securities provides complete information and guidance on the latest developments in the burgeoning sukuk securities markets. Written by leading Islamic finance experts, this essential guide offers insight into the concepts, design features, contract structures, yields, and payoffs in all twelve global sukuk markets, providing Islamic finance professionals with an invaluable addition to their library. The first book to fully introduce the market, this book provides a detailed overview of the sukuk market, with practical guidance toward.
Front Matter -- The Foundation of. Introduction to Sukuk Markets -- Securities: Definitions, Classification, and Pricing Issues -- Pragmatic and Idealistic Approaches to Structuring -- Contract Design and the Structure of Common Securities Issued to Date -- Samples of Issued -- Contract Design and the Structure of Securities Yet Issued -- Securities and Conventional Bonds -- Securities in Practice. Regulations with a Difference -- Securitization, Trading, and Rating -- Worldwide Markets -- Regulatory Issues for Financial Products -- Payoff Structures and . The Foundation and Principles of Islamic Finance -- Cash-Flow Identification and Pattern Recognition for Theoretical Valuation Models -- A Matter of Choice: or Bond? -- Challenges and Future Developments.
Includes bibliographical references and index.
Print version record.
Keywords: Securities -- Islamic countries; Investments -- Islamic countries; Electronic books